ANALISIS EFISIENSI PEMASARAN AGROINDUSTRI KLANTING DI KECAMATAN NEGERI KATON KABUPATEN PESAWARAN - Radot Vernando Siburian; Ktut Murniati; Ani Suryani (Lampung University, 2019)
This research aims to know how much income of producer of klanting agroindustry, marketing channels, and the efficiency of klanting agroindustry marketing at Karang Rejo Village, Negeri Katon Subdistrict, Pesawaran Regency, and Lampung Province. The research is conducted by a survey method. The total of respondents is 32 producers and 146 merchants. The research data was collected in December 2016 until March 2017 and analyzed by descriptive qualitative and quantitative. The result showed that the amount of klanting agroindustry producers’ income was Rp2,018,932.67/month with R/C 1.38 on cash and Rp1,649,645.49 /month with R/C 1.29 on total cost. It meant that the klanting agroindustry was feasible to be run. In addition, there were four kinds of marketing channels on klanting agroindustry at Karang Rejo Village. Marketing system of klanting agroindustry was still not efficient, because the value of elasticity transmission price was less than one.Key words: agroindustry, efficiency, klanting, marketing